The mountainous pastoral livestock farming in Tzoumerka, Epirus: The economic dimension of activity and the sustainable management of pasturelands - Roukos Ch.; Kontogeorgos A.; Chatzitheodoridis F.; Kandrelis S. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
The aim of this paper is to depict the structural characteristics of livestock farms in the area of the Pindos Mountain. A questionnaire survey held in June 2013 was used to examine 75 out of a total of 441 heads of livestock farms, mainly pastoral, in order to identify their attitudes and perceptions about their income, professional satisfaction, as well as their practices that ensure the sustainability of mountainous pasturelands. The results show that most of the farmers are not satisfied by the subsidies they receive through the Common Agricultural Policy; even more, they are not familiar with the regulatory requirements of the cross compliance, while the majority of them believe that the current payment system (decoupling) is not fair and is not conducive to livestock farming. Thus, they seem to be dissatisfied with their income. Finally, the participants claim that they are not satisfied with the low forage production as a result of overgrazing of mountainous pasturelands. Moreover, they are willing to pay a higher rent for the pasturelands in case of improved technical infrastructure and increased forage production.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)